Analisis Dampak COVID 19 terhadap PDRB Provinsi Bali dengan Model Intervensi - Mega Silfiani; Farida Nur Hayati; Surya Puspita Sari; Agung Prabowo (University of Mataram, 2022)
COVID 19 is a disease caused by SARS-CoV-2. This virus spread very quickly to almost all countries including Indonesia. Bali tourism has developed in such a way and contributed greatly to regional development directly or indirectly. Gross Regional Domestic Product or GRDP has an important role in increasing the economic growth of a region, where the higher the GRDP, it can be said that the economic growth is also high. This study aims to analyze the impact of COVID 19 on the GRDP of the Province of Bali using an intervention model. The data used in this study is secondary data from quarterly GRDP on the basis of current prices in the accommodation, food and drink sector. Data was collected from the first quarter of 2010 to the fourth quarter of 2021. Based on the modeling that has been carried out with the intervention model, the best model to predict the impact of COVID 19 on GRDP in Bali Province is ARIMA(0,1,0)(1,0,0)4 r=1 with SMAPE value of 8.327 and MdAPE of 0.067.